MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI TARI KREASI PADA ANAK USIA 5-6 TAHUN DI TK KASIH IBU SINTONG KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Wahyuni Wahyuni; Daviq Chairilsyah; Febriliasmanto Febriliasmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: background of this study is the lack of ability of children in rough motor skills. Some children may not be able to perform coordinated body movements to train flexibility, balance and agility, some children may not be able to coordinate the movement of hand-foot-head, in imitating the dance. Therefore, it is necessary efforts to improve gross motor skills of children in dance creations that butterfly dance. The purpose of this study was 1) to determine how to create the flexibility of the child's body through dance creations with dance training so that the child's body can dance properly, 2) to determine the application of dance creations to enhance the flexibility of the muscles of the children aged 5-6 years di tk. Kasih ibu sintong rokan hilir, 3) to determine the dance creations can improve rough motor skills of children aged 5-6 years in tk kasih ibu sintong, 4) to find out how high the increase in rough motor skills of children through dance creations. This type of research is classroom action research conducted in two cycles, namely cycle i and cycle ii. In each cycle consists of four phases: planning, action observation, reflection, data collection tools used in this study is the observation sheet form. The number of subjects in this study were 20 children that consist of 15 girls and 5 boys. Based on the analysis of the assessment process there was an increase of 2 cycles. Improvement occurred, is from before action to the first cycle was 65.68%, cycle i cycle ii amounted to 30.62% and as well as the improvement of the prior cycle to the second cycle of 116, 40%. From the results of these studies concluded that through dance creations can improve gross motor skills of children aged 5-6 years in tk kasih ibu sintong.Keywords: Improving Kids Rough Motor Skills Childhood 5-6 Years, Through Creative Dance.